ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PADA HOTEL BERBINTANG DI BATAM - April Lyvia; Evi Silvana Muchsinati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study is aimed to determine the effect of recruitment, training and development, compensation and job satisfaction to employee performance of four star hotel’s employees in Batam. This study was conducted by distributing questionnaires to 273 respondents who are employees of four star hotels in Batam. The questionnaires were distributed and collected back, and 261 questionnaires were filled out completely so that it can be used for regression analisys by using Partial Least Squares. From the data processing with PLS is known that there are relationships between all the variables studied. Based on this research, the results obtained indicate that the compensation variable has a significant effect on the job satisfaction variable, job satisfaction has a significant effect on employee performance, the performance appraisal variable has no significant effect on the job satisfaction variable, the recruitment variable has a significant effect on job satisfaction and the training variable and development has no significant effect on job satisfaction. Keywords: employee performance, recruitment, training and development, compensation, performance appraisal, job satisfaction